OPTIMIZING QUALITY FUNCTION DEPLOYMENT AT SANTRI BOARDING HOUSES TO IMPROVE THE QUALITY OF SERVICES PESANTREN - Rizal, Muhammad Abu Zainur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The use of media and learning methods is the right solution for teacher educators to develop students' skills. The media most likely to be implemented in schools is the use of audiovisual media. The aim of this research is to determine the process of using audiovisual learning media in teaching speaking skills to high school students, of course not only the school but all institutions must utilize the media in the most creative way possible. Apart from being interesting, it is also useful in increasing students' interest in learning, it also helps to develop students' hard skills and soft skills. There are also many types of media that can be used, including: audio media, visual media and audiovisual media. In institutions with Islamic boarding school nuances or in Islamic boarding schools, such as what researchers conducted at SMA Nurul Jadid Paiton Probolinggo. This research was carried out for learning because it utilizes available technology to channel the writer's abilities in the field of creation, especially in audiovisual media which will be distributed to help the teaching and learning process in improving students' interest in learning to be more creative in learning.